2017
DOI: 10.1038/srep45550
|View full text |Cite
|
Sign up to set email alerts
|

Irreversibility transition of colloidal polycrystals under cyclic deformation

Abstract: Cyclically loaded disordered particle systems, such as granular packings and amorphous media, display a non-equilibrium phase transition towards irreversibility. Here, we investigate numerically the cyclic deformation of a colloidal polycrystal with impurities and reveal a transition to irreversible behavior driven by the displacement of dislocations. At the phase transition we observe enhanced particle diffusion, system size effects and broadly distributed strain bursts. In addition to provide an analogy betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…We expect that the present work will stimulate further research on RIT, e.g., in the presence of isotropic shear where smectic flow is considered to be absent, and on nonequilibrium phase transitions in various many-particle systems, including colloidal particles 52,53 or dense, jammed systems 28,5459 .…”
Section: Resultsmentioning
confidence: 94%
“…We expect that the present work will stimulate further research on RIT, e.g., in the presence of isotropic shear where smectic flow is considered to be absent, and on nonequilibrium phase transitions in various many-particle systems, including colloidal particles 52,53 or dense, jammed systems 28,5459 .…”
Section: Resultsmentioning
confidence: 94%
“…Any further distribution of this work must maintain attribution to the author(s) and the title of the work, journal citation and DOI. the colloidal particles, such as granular matter [18][19][20][21], dislocations [22,23], amorphous solids [24][25][26][27], polycrystalline solids [28], charged colloids [29], and vortices in type-II superconductors [30][31][32]. The dynamics of most of these systems is overdamped, and little is known about how nondissipative dynamics would affect a reversible to irreversible transition.…”
mentioning
confidence: 99%
“…They evolve with the atomic rearrangement. However, the presence of bigger particles makes the boundary stronger as we showed in our previous work [23]. In the case of an amorphous solid, there is no long-range ordering.…”
Section: Model and Simulation Detailsmentioning
confidence: 59%
“…To understand the energy dissipation during the plastic events, one computes the hysteresis loop area from the shear stress against the applied strain. In our previous study, we have shown that the hysteresis loop area sharply increases as strain amplitude reaches a threshold value in case of a polycrystalline system [23]. In a similar study, Laurson et al [40] have shown that cyclically stressed crystalline solids exhibit two phases: jammed and the moving state by computing hysteresis loop area.…”
Section: B Dynamic Modulusmentioning
confidence: 70%
See 1 more Smart Citation